Engineering drawing and design - Madsen, David A. (Delmar, 1991)
This text explores the entire field of engineering drawing with a thorough examination of mechanical drawing. The text is comprehensive, avoiding the highly technical/formal method used by other texts in the field. This book should be of interest to students at FE colleges studying engineering.